Cadmium sulfide nanostructures: influence of morphology on the photocatalytic degradation of erioglaucine and hydrogen generation - Shenoy, Sulakshana; Jang, Eunyong; Park, Tae Joo; Gopinath, Chinnakonda S.; Sridharan, Kishore (Applied Surface Science, 2019)
Size and shape of inorganic materials are known to have great effects on their physical and chemical properties. Here, for the first time we report the visible light driven photocatalytic degradation of erioglaucine - a stable organic dye molecule in the presence of chemically synthesized nanoscale CdS with 1D (nanorods), 2D (nanosheets) and 3D (hierarchical) morphology. Visible light driven photocatalytic degradation efficiency of both 1D and 3D CdS in the removal of erioglaucine are identical. Surprisingly, with 5 min of sonication, the highly crystalline 3D CdS stacked with many thin nanowires containing numerous active surface sites exhibited fourfold enhanced photodegradation efficiency in comparison to 1D and 2D CdS. Scavenger studies revealed that electrons and superoxide radicals are primary reactive species involved in the photodegradation of erioglaucine, while cyclic photodegradation studies revealed the good stability of 3D CdS against photocorrosion. Further, the photocatalytic hydrogen evolution studies also revealed the excellent activity of 3D CdS in comparison to 1D and 2D CdS. Thus, we find that the morphology indeed influences the photocatalytic activity. These results reveal that 3D CdS nanostructures investigated in the present work are efficient photocatalysts that could be fine-tuned for both environmental remediation and hydrogen generation applications.
Keywords: Cadmium sulfide; Erioglaucine; Hydrogen evolution; Nanostructures; Photocatalysis

One-dimensional multichannel g-C3N4.7 nanostructure realizing an efficient photocatalytic hydrogen evolution reaction and its theoretical investigations - Antil, Bindu; Kumar, Lakshya; Ranjan, Ravi; Shenoy, Sulakshana; Tarafder, Kartick; Gopinath, Chinnakonda S.; Deka, Sasanka (ACS Applied Energy Materials, 2021)
The emerging metal-free carbon nitride (C3N4) offers prominent possibilities for realizing the highly effective hydrogen evolution reaction (HER). However, its poor surface conductivity and insufficient catalytic sites hinder the HER performance. Herein, a one-dimensional vermicular rope-like graphitic carbon nitride nanostructure is demonstrated that consists of multichannel tubular pores and high nitrogen content, which is fabricated through a cost-effective approach having the final stoichiometry g-C3N4.7 for HER application. The present g-C3N4.7 is unique owing to the presence of abundant channels for the diffusion process, modulated surface chemistry with rich- electroactive sites from N-electron lone pairs, greatly reduced recombination rate of photoexcited exciton pairs, and a high donor concentration (4.26 x 10(17) cm(3)). The catalyst offers a visible-light-driven photocatalytic H-2 evolution rate as high as 4910 mu mol h(-1)g(-1) with an apparent quantum yield of 14.07% at band gap absorption (2.59 eV, 479 nm) under 7.68 mW cm(-2) illumination. The number of hydrogen gas molecules produced is 1.307 x 10(15) s(-1) cm(-2), which remained constant for a minimum of 18 h of repeated cycling in the HER without any degradation of the catalyst. In density functional theory calculations, a significant change in the band offset is observed due to N doping into the system in favor of electron catalysis. The theoretical band gap of a monolayer of g-C3N4.7 was enormously reduced because of the presence of additional densities of states from the doped N atom inside the band gap. These impurity or donor bands are formed inside the band gap region, which ultimately enhance the hydrogen ion reduction reaction enormously.
Keywords: carbon nitride; Density functional theory; hydrogen evolution reaction; nitrogen-rich; Photocatalyst